The impact of COVID-19 pandemic on South Asian stock markets - Jesus-Silva, N. (2023)
The main aim of this paper is to analyze the impact of the world pandemic COVID-19 on the efficiency of capital markets in countries of South Asia, namely, the market efficiency of these stock markets in the pre and post-COVID-19 global wave. The method includes an econometric model based on time series analysis. Information and data come from the stock indices of Asian countries from July 2018 to July 2021. The results confirm that despite all financial markets presenting efficient results before the global outbreak, after the COVID-19 pandemic, all the financial markets reduced efficiency, as expected. These results benefit the regulators of financial markets and investors to forecast and anticipate adjusted financial measures and policy decision-makers.